2020
DOI: 10.1103/physrevb.102.100202
|View full text |Cite
|
Sign up to set email alerts
|

Absence of slow particle transport in the many-body localized phase

Abstract: We analyze the saturation value of the bipartite entanglement and number entropy starting from a random product state deep in the many-body localized (MBL) phase. By studying the probability distributions of these entropies we find that the growth of the saturation value of the entanglement entropy stems from a significant reshuffling of the weight in the probability distributions from the bulk to the exponential tails. In contrast, the probability distributions of the saturation value of the number entropy ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 44 publications
2
35
0
Order By: Relevance
“…[30,31] that the system is not localized up to at least D ∼ 40. While we already responded to the criticism of our results by Luitz and BarLev [53] in detail in [31] our current study has brought to light another issue: Performing averages over all initial product states leads to a 1/L correction to ∆N 2 with a negative sign which is present already in the non-interacting Anderson case and which can disguise the increase of ∆N 2 with system size in the interacting case. This might explain why this increase has been missed in the past including in [53].…”
Section: Discussionmentioning
confidence: 55%
“…[30,31] that the system is not localized up to at least D ∼ 40. While we already responded to the criticism of our results by Luitz and BarLev [53] in detail in [31] our current study has brought to light another issue: Performing averages over all initial product states leads to a 1/L correction to ∆N 2 with a negative sign which is present already in the non-interacting Anderson case and which can disguise the increase of ∆N 2 with system size in the interacting case. This might explain why this increase has been missed in the past including in [53].…”
Section: Discussionmentioning
confidence: 55%
“…Next, our probe could be relevant in the recently emerging debate on (2) (0, 0|1000) as a function of for L = 8 (squares), L = 10 (circles), and L = 12 (pentagons). For Poissonian and Wigner-Dyson level statistics, one expects, respectively, ρ (2) (0, 0|1000) = 1 and ρ (2) (0, 0|1000) ≈ 0.001. the stability of many-body localization [19,[44][45][46], in which the spectral form factor plays a prominent role. We remark that the spectral form factor appears in the survival probability for fully ergodic systems [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…17 stimulated a flurry of numerical studies [18][19][20][21] of S N in the Hesenberg model at strong disorder (considered to be deep in the MBL phase), fitting the numerical data by a slow growth of S N ∼ ln ln t (this growth of S N is unrelated to a subleading 22 ∼ ln ln t growth of von-Neumann entropy in a dephasing model of MBL) and arguing that this growth is unbounded which would challenge the established MBL phenomenology, specifically no particle transport in the localized phase. A subsequent study focusing on the steady-state saturation value of S N on the other hand concluded 23 that there are no signs of ergodicity and that S N is compatible with MBL.…”
Section: Introductionmentioning
confidence: 99%